A Comparative Study of Writing Apprehension Levels Among Two Cohorts of Pre-Service Teachers - Aninda Marsa Purnama Putri; Moh Hasbullah Isnaini (English Teaching Journal : A Journal of English Literature, Language and Education, 2025)
This study examined whether writing apprehension levels are different between the cohorts of batch 2024 and 2025 at Universitas Brawijaya. The study employed a comparative study as the design. The data were collected from 110 participants, with 55 from each batch, using questionnaires adopted from Daly & Miller, comprising of 20 items that implement a Likert scale. Data were analyzed through descriptive statistics and an independent samples t-test, preceded by normality and homogeneity checks. The results indicate that the distribution is normal, but the result of the independent samples t-test is not significant since the gain p-value is .184, which is greater than .05. The results of this study suggest that the length of writing exposure does not affect the level of writing apprehension of the pre-service teachers of the two cohorts. Since additional writing exposure did not decrease the writing apprehension, teacher education programs should incorporate a strategy that focuses on anxiety-reduction rather than rely on accumulated coursework alone.